Effects of Pharmacist-Led Interventions Regarding Adult Patients with Type 2 Diabetes Mellitus in Mexico: A Systematic Review - Dulce D. Blanco-Vega; Alfonso Reyes-López; Jessica L. Vargas-Neri; Frida I. Osnaya-Valencia (MDPI AG, 2024)
In Mexico, type 2 diabetes mellitus (T2DM) is a serious public health concern. As experts in drug therapy, pharmacists are essential additions to multidisciplinary diabetes patient care teams. There have been no systematic reviews or meta-analyses performed on pharmacist-led interventions (PIs) in Mexico; therefore, the impact of PIs on patients remains poorly explored. An electronic search of the PubMed, SciELO and BVS databases and certain institutional repositories was conducted in English and Spanish through 24 August 2021 with a subsequent update through June 2024. A total of 1302 potentially relevant studies were identified in the initial search, of which nine met the eligibility criteria and were included in this systematic review. The results suggest that PIs, such as pharmacotherapeutic follow-up and patient education, may have positive effects on outcomes in Mexican patients with T2DM. PIs led to significant reductions in glycosylated hemoglobin, fasting blood glucose, triglycerides, total cholesterol, LDL cholesterol and arterial blood pressure levels, general reductions in body mass index and negative outcomes associated with medication, as well as significant improvements in therapeutic adherence and patient knowledge in the intervention group during follow-up periods of 3-12 months. Further well-designed research, including controlled studies with adequate sample sizes and standardized tools, is essential to fully understand the effects of PIs regarding patients with T2DM in Mexico.